Early-diverging plesiosaurs from the Pliensbachian (Lower Jurassic) of northwestern Germany - Sven Sachs; Jahn J. Hornung; Daniel Madzia (PeerJ)
The knowledge of Pliensbachian (Early Jurassic, ∼192.9–184.2 Ma) plesiosaurs is notoriously insufficient. Although there have been specimens described from different parts of the world, only three of them have been established as diagnosable taxa. Here, we describe two previously unreported lower Pliensbachian plesiosaur occurrences that originate from two sites located in North Rhine-Westphalia, Germany. One of the new occurrences is represented by three cervical and three indeterminable vertebrae from Werther, the other includes two associated pectoral or anterior dorsal vertebrae from Bielefeld. Although highly incomplete, the Werther individual, which derived from the Uptonia jamesoni Zone, is found to represent the only reliably identified early Pliensbachian pliosaurid known to date. Its material is geographically and stratigraphically proximate to the late Pliensbachian pliosaurid Arminisaurus schuberti, found in a clay-pit located in the Bielefeld district of Jöllenbeck. However, even though the Werther plesiosaur and A. schuberti show a broadly similar morphology of the preserved cervical section, a precise identification of the Werther taxon is currently impossible.